Rhode Island Domestic Violence Shelter Policies, Practices, and Experiences Pertaining to Survivors With Opioid Use Disorder: Results of a Qualitative Study - Emily F Rothman; Rebecca Stone; Sarah M Bagley (SAGE Publishing, 2018)
The purpose of this study was to fill a gap in the existing research by exploring policies and practices of domestic violence shelters in one US state pertaining to clients with opioid use disorders (OUDs), as well as documenting some of their experiences providing services to those clients. We used semi-structured key informant interviews to gather information about Rhode Island shelter practices and policies pertaining to OUD-relevant topics and make meaning of shelter workers' experiences with clients with OUDs. One researcher conducted all 30-min, telephone interviews. Qualitative data were analyzed using a content-based analysis approach. The open-ended interview questions yielded information that clustered in the following three main themes: (1) existing shelter policies and practices; (2) staff training on OUDs; and (3) ideas for improvement. Intimate partner violence (IPV) service providers reported that OUD is an issue that affects their clientele, creates problems for both IPV survivors and for staff who are helping them heal from IPV, and causes concerns about the safety of children and other shelter residents who may be housed with individuals with OUDs. Participants reported a range of policies and practices related to how IPV survivors with OUDs are served by their programs. They also offered multiple possible improvements that could be made to IPV survivor programming. Among their suggestions were the establishment of long-term housing, hiring substance use disorder specialists to work in IPV shelters, and improving interagency relationships between IPV programs, child protection services, and substance use disorder treatment providers. Some close-ended interview questions permitted calculations about the percentage of programs that had particular policies in place. For example, of the six programs, 50% (n = 3) reported that they keep naloxone on site. Only one of the six programs (18%) reported that they have a protocol for disposing of unused opioids, medications for OUD, or drug paraphernalia if it is found at the shelter. Additional data about the prevalence of OUDs among the IPV shelter population is needed, as are in-depth analyses of barriers and facilitators to OUD treatment for IPV survivors.